APLIKASI MOBILE SMS GATEWAY OVER GPRS UNTUK MENGAKSES SISTEM INFORMASI - Wahyu Pujiyono; Arif Rahman; Ananta Wijaya (Universitas Ahmad Dahlan, 2009)
SMS via GPRS technology can be used to access data from information systems. This technology is one of regular and premium SMS extensions. The SMS over GPRS is composed by three components: the mobile application, server, router and gateway of information systems. The research objective was to build a mobile application to access information systems with the assumption that the server and the gateway router of information systems already exist. System was built using the http protocol, which has a request-response mechanism. There are two methods in the delivery of the message (request) and the receipt of the message (response) from the server, the message filtering and message parsing. Filtering is used to filter the message text /string that not known to be a string known by http, and then in message parsing process, message parses in the form of XML.